Effect of electric field on the polarised infrared spectra of smectic liquid crystals - Jamshidi, Mohammad Mehdi (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2000)
In this research Fourier Transform Infrared Spectroscopy has been used to investigate the effect of the polarised infrared beam and the electric field on the orientational behaviour of the ferroelectric and antiferroelectric liquid crystals. For this, infrared spectra are measured as a function of the polariser angle as the bias voltage to liquid crystal cells was altered.
Keywords: Electrical and Electronic Engineering, Ph.D.; Ph.D. Trinity College Dublin